2015
DOI: 10.1038/jid.2014.454
|View full text |Cite
|
Sign up to set email alerts
|

CD271 Mediates Stem Cells to Early Progeny Transition in Human Epidermis

Abstract: CD271 is the low-affinity neurotrophin (p75NTR) receptor that belongs to the tumor necrosis factor receptor superfamily. Because in human epidermis, CD271 is predominantly expressed in transit-amplifying (TA) cells, we evaluated the role of this receptor in keratinocyte differentiation and in the transition from keratinocyte stem cells (KSCs) to progeny. Calcium induced an upregulation of CD271 in subconfluent keratinocytes, which was prevented by CD271 small interfering RNA. Furthermore, CD271 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…In addition, p75 NTR -positive TA cells display a higher proliferative capacity and a better colony forming efficiency, as compared to p75 NTR -negative cells. Finally, human reconstructed epidermis derived from p75 NTR -positive TA cells express markers of early differentiation (73). This indicates that p75 NTR identifies a population of early TA cells.…”
Section: P75ntr and Epidermal Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, p75 NTR -positive TA cells display a higher proliferative capacity and a better colony forming efficiency, as compared to p75 NTR -negative cells. Finally, human reconstructed epidermis derived from p75 NTR -positive TA cells express markers of early differentiation (73). This indicates that p75 NTR identifies a population of early TA cells.…”
Section: P75ntr and Epidermal Homeostasismentioning
confidence: 99%
“…In fact, silencing p75 NTR prevents calcium-induced keratinocyte differentiation and converts TA cells into a KSC phenotype. Moreover, overexpression of p75 NTR in KSC results in a keratinocyte subpopulation with the features of TA cells (73). These results indicate that p75 NTR could act as a “switch on-off” protein that critically regulates KSC-progeny transition and differentiation in human epidermis (Figure 1).…”
Section: P75ntr and Epidermal Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The CD271 positive ASCs may retain the sphere-forming ability of NCSCs on chitosan which separate them from the CD271 negative cells on chitosan. On the other hand, literature has indicated that CD271 was upregulated in subconfluent keratinocytes under high calcium conditions [52]. In our previous study, we found that calcium binding capacity of chitosan membranes was found to change the cell-substrate and cellecell interactions to modulate the process of spheroid formation.…”
Section: Discussionmentioning
confidence: 98%
“…p75NTR, a member of tumor necrosis factor receptor superfamily, comprises three domains, including an extracellular domain, a transmembrane domain, and an intracellular domain. Of three domains, the extracellular domain has four cysteine rich repeats, and is required for interaction of NGF-p75NTR [17][18][19]. Once NGFp75NTR compounds occur, p75NTR can regulate cell apoptosis, proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%